Theatres of violence : massacre, mass killing, and atrocity throughout history - Dwyer, Philip G.; Ryan, Lyndall, 1943- (War and genocide, 2012)
Massacres and mass killings have always marked if not shaped the history of the world and as such are subjects of increasing interest among historians. The premise underlying this collection is that massacres were an integral, if not accepted part (until quite recently) of warfare, and that they were often fundamental to the colonizing process in the early modern and modern worlds. Making a deliberate distinction between 'massacre' and 'genocide', the editors call for an entirely separate and new subject under the rubric of 'Massacre Studies', dealing with mass killings that are not genocidal.